2016
DOI: 10.23960/j.hptt.11671-81
|View full text |Cite
|
Sign up to set email alerts
|

Kerentanan Wereng Batang Cokelat (Nilaparvata Lugens) Dari Enam Lokasi Di Pulau Jawa Terhadap Tiga Jenis Insektisida

Abstract: Susceptibility of the rice brown planthopper (Nilaparvata lugens) from six locations in Java to three insecticides. The rice brown planthopper (BPH), Nilaparvata lugens (Stål) (Hemiptera: Delphacidae), is one of the important rice pests in Indonesia. Despite relatively frequent use of insecticides to control this pest, data on BPH resistance to insecticides commonly used by farmers in Indonesia is scarce. This study was conducted to assess the susceptibility of BPH from six locations in Java to three insectici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…These results indicate that the population of N. lugens from Karanganyar is the most sensitive to pymetrozin. According to Surahmat et al (2016), the insecticide pymetrozine does not have a knockdown effect, but works quickly to control sucking insects by inhibiting eating.…”
Section: Determination Of Lc50 N Lugens Field Population Against Pymetrozine Insecticidementioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that the population of N. lugens from Karanganyar is the most sensitive to pymetrozin. According to Surahmat et al (2016), the insecticide pymetrozine does not have a knockdown effect, but works quickly to control sucking insects by inhibiting eating.…”
Section: Determination Of Lc50 N Lugens Field Population Against Pymetrozine Insecticidementioning
confidence: 99%
“…Pymetrozine is a new insecticide that being used in Indonesia recently. So far, pymetrozine does not have a knockdown effect and acts as an inhibitor for eating (Surahmat et al, 2016). The active ingredient of the pimetrozine insecticide belongs to group 9B and represents pyridine azomethine derivates (IRAC, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…quinalphos, carbofuran, monocrotophos, carbaryl phorate, phosphamidon, chlorpyriphos and BPMC. IRRI also recommends that deltamethrin should not be for BPH control because it causes resurgence (Surahmat, Dadang, & Prijono, 2016). Furthermore, Basanth, Sannaveerappanavar, & Gowda (2013) conducted research using several insecticides and they found that the level of insecticide resistance was varied in each region.…”
Section: The Relationship Between Bph Attacks and Insecticides Use Pattern In Javamentioning
confidence: 99%
“…Pymetrozine has become an important insecticide for controlling the BPH since fipronil was forbidden to use in 2009 [18]. Pymetrozine belongs to group 9B and represents pyridine azomethine derivatives [19], and has no knockdown effect and is an inhibitor of feeding activity [20]. Pymetrozine has the common name (E)-4,5-dihydro-6-methyl-4-(3 pyridylmethylene amino)-1,2,4-triazine-3 (2H)one has low acute toxicity by oral, dermal and inhalation routes.…”
Section: Introductionmentioning
confidence: 99%